Development of Mandailing Culture-Based Learning Devices with an Open-Ended Approach to Improve Students 'Mathematic Connection and Self-Efficiency Abilities SMPN 2 Batangtoru - Ajizah Siregar; Bornok Sinaga; Hermawan Syahputra (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to: 1) describe learning tools with an open-ended approach that meets the criteria of being valid, practical, and effective; 2) Describe the improvement of mathematical connection ability using learning tools with the developed open-ended approach; 3) Describe the increase in ability self efficacy by using learning tools with the developed open-ended approach. This research is a development research conducted in two stages. Learning tools produced from this research are: Learning Implementation Plan (RPP), Student Worksheet (LKPD), Student Book (BS), mathematical connection ability test and questionnaire. Self efficacy students. From the results of the first trial and second trial, it was obtained: 1) the learning device with the Open-ended approach developed had been meet the criteria of being valid, practical, and effective in terms of their respective criteria;2) there was an increase in the students' mathematical connection ability using learning tools with an open-ended approach developed in the first trial, obtaining an average posttest score of 61.76, and an increase in the second trial with an average posttest score of 82.35; 3) there is an increase in ability self efficacy students using learning tools with an open-ended approach developed in the first trial obtained a value of 68.64 and increased in the second trial with a value of 87.52. Based on the results of the study it is suggested that mathematics teachers strive for mathematics learning using an open-ended learning approach and the learning tools developed can improve mathematical connection skills and self efficacy students in mathematics learning.